Slope monitoring and slope failure threshold determination at KM46 Jalan Simpang Pulai-Cameron Highlands, Malaysia - Azmi, Nur Anati (2015)
In Malaysia, landslide is one of the common natural disasters and a growing public concern, especially for the people who frequent the hilly road or mountainous terrain. There are many factors that cause landslides such as groundwater level, geological properties such as type of rocks, soil, joint, and fault, slope condition, and geometry of slopes. The objectives of this research can be divided into four objectives. First objective is to develop a geological-geotechnical-geomorphologic map of the study area. The second objective which is to identify the mode of failure within the study area and within the Pos Selim area can be achieved using all the parameters involved from first objective. The third objective is to analyze the slope monitoring data from geotechnical equipments that can be retrieved wirelessly. Lastly, threshold values for the slope failure risk potential can be determined. The slope chosen is the KM 46 Jalan Simpang Pulai-Cameron Highlands in Perak. The slope was monitored using the Wireless Sensor Network (WSN). Geology of the area mainly consists of granite and schist which are moderately to highly weathered and the schist area had complex structures which are highly fractured. Slope monitoring instruments were installed at the site of selected locations. Surface extensometers (SEM) were installed to measure the ground displacement. Inclinometers (IPI) used to monitor the subsurface or underground movement. Vibrating wire piezometers (VWP) and rain gauge, (RG) were installed to measure the ground water level and rainfall intensity. Some of the instruments were installed at different depth in boreholes while the SEM was located on the slope. All these instruments were connected to wireless devices and data from the instruments were directly sent wirelessly to the users through a web. A reliable and justified combination of the parameters obtained was developed into an equation that can be used to obtain the threshold value. A Risk Level Guide, which is categorized into “LOW”, with threshold value less than 0.8, while “MEDIUM” between 0.8 to 1.6 and “HIGH” was more than 1.6. This guide is based on the threshold values obtained and special considerations are also placed on the qualitative aspects such as discontinuity analysis. This guide can be used as another source to trigger the alarm system by the local authorities at the site apart from other methods such as visual inspection of the soil movements.